Test Conditions of Diesel Engine Particulate Emission and the Results Obtained - Jerzy Cisek; Zygmunt Szlachta; Marian Marian Zabłocki (Communications - Scientific letters of the University of Zilina, 2001)
In this work, based on experimental results, the effect of four factors of particulate emission measurements were taken into account: the method of determining the exhaust dilution in a diluting tunnel, the ratio of exhaust gases dilution, conditioning of the filters used in particle emission measurements and isokinetics of sampling a diluting tunnel.The results presented in this paper concern four chosen parameters characterizing conditions of the measurement of particle emissions. Obviously, this data does not close the question of influence on other parameters on their result measurements. They show, however, the necessity of more detailed specification on the protocol of measurements to enable comparison of various results. It is particularly important during measurements of small emissions of particles in the range expected by the rules of EURO-III and EURO-IV. It seems that the replacement of the R-49 standard by a new test cycle ESC or ETC should become a good opportunity for a deep analysis of the methods of experiments, in relation to the repeatability and reproducibility of the results.